KUALITAS PAPAN SEMEN DARI SERUTAN LIMBAH INDUSTRI PENSIL DENGAN BERBAGAI KOMPOSISI BAHAN BAKU DAN KONSENTRASI CaCl2 - Fatmala Salmah; Luthfi Hakim; Tito Sucipto (Program studi Kehutanan USU, 2015)
This research concerning on the use of pencil shavings waste as a raw material in the manufacture of cement board. The purpose of this research was to evaluate the quality of the cement board to the physical properties and mechanical properties of the board with different ratio of raw materials:cement and various concentrations of CaCl2 as a catalyst. The board was made of pencil shavings with various ratio of raw materials (cement : shave ) were : 75:25; 80:20; 85:15 and a catalyst concentration were 3 % and 5 % with a target density of 1,2 kg/cm3. Testing of physical and mechanical properties based on the standard JIS A 5417-1992 of cement particle board . The results of this research indicate that the physical properties of the cement board pencil shavings particle has met the standard of JIS A 5417-1992 . As for testing the mechanical properties do not meet the standards of JIS A 5417-1992 . The best treatment is 85:15 raw material composition at a concentration of 3 % catalyst. Comparison of the composition of raw materials and catalyst concentration does not significantly affect the physical and mechanical properties of the cement board particles pencil shavings . Keywords : cement board , catalysts , particle , pencil shavings , CaCl2